Hospital obstetric practices and their repercussions on maternal welfare - Alvares, Aline Spanevello; Paula Correa, Aurea Christina de; Tomiyoshi Nakagawa, Janete Tamami; Valim, Marilia Duarte; Jamas, Milena Temer [UNESP]; Knupp Medeiros, Renata Marien (Univ Sao Paolo, 2020)
Objective: To analyze the association of care practices performed by obstetric professionals with maternal welfare/malaise levels. Method: A quantitative study conducted in a Prepartum/Childbirth/Postpartum Unit of a Teaching Hospital with puerperal women who underwent vaginal births. An association was performed between obstetric practices and maternal welfare/malaise levels. Results: There were 104 puerperal women who participated. Obstetric practices which caused mothers to feel unwell and which obtained statistical significance were: amniotomy (p = 0.018), episiotomy (p = 0.05), adoption of horizontal positions in the expulsive period (p = 0.04), the non-use of non-invasive care technologies (p = 0.029), and non-skin-to-skin contact between mother and child (p = 0.002). For most women, the presence of a companion favored welfare, even though it did not have a statistically significant association. After performing logistic regression, non-performance of amniotomy was the only variable which showed significance in maternal welfare. Conclusion: Humanized obstetric practices have greater potential to promote maternal welfare. The importance of obstetric nurses conducting practices which provide greater welfare to mothers is emphasized.
Keywords: Maternal Welfare; Obstetric Nursing; Humanizing Delivery; Maternal-Child Nursing